Contemporary review of prognostic markers of prostate cancer from a pathologist perspective - Elias, Martin; Bouchal, Jan; Kral, Milan; Kurfurstova, Daniela (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2025)
Prostate cancer is the most frequently diagnosed malignant tumour in men worldwide. To treat this condition, prognostic markers to distinguish indolent from aggressive disease, and biomarkers for metastatic forms are needed. From a pathologist's perspective, despite the plethora of emerging biomarkers, none to date has made its way into clinical practice. The need for prognostic and predictive markers following histological evaluation remains. This overview of some putative immunohistochemical and genetic markers reveals the pitfalls of biomarker research, notably verifiability, validity and interlaboratory comparison. Meta-analyses and extensive cooperation between pathology departments are a sine qua non. Codes of Best Practice such as the REMARK guidelines have been advocated as a path forward. Currently, the most widely used and validated prognostic marker remains the Gleason score. Ki67 along with PTEN are the most promising prognostic markers.
Keywords: Prognosis; patologové; Male; lidé; Humans; Neoplasm Grading; Gleason score; prognostic and predictive markers; Biomarkers, Tumor; nádorové biomarkery; PTEN Phosphohydrolase; prostate biopsy; immunohistochemistry; Prostatic Neoplasms; Pathologists; fosfohydroláza PTEN; prostate adenocarcinoma; mužské pohlaví; nádory prostaty; antigen Ki-67; Ki-67 Antigen; stupeň nádoru; prognóza; radical prostatectomy